An introduction to grounded methodology for emerging educational researchers - Hayhoe, Simon (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Introducing the reader to grounded methodology and its ethical approach, this book explores the theory behind the method as well as how to use it to develop and evaluate learning and education projects. Covering data collection techniques used in the course of education research such as: observations, interviews, course development, participant diaries and online data collection, this book investigates the practical realities of researching in education contexts and the differences in educational, national and cultural backgrounds. It is ideal reading for students and academics looking to update and increase their knowledge on grounded methodology"--
"Routledge Focus" -- Cover.
OCLC-licensed vendor bibliographic record.
Keywords: Education -- Research -- Methodology; Education -- Data processing; EDUCATION / General